2007
DOI: 10.1111/j.1574-6968.2007.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

EspP, a Type V-secreted serine protease of enterohaemorrhagicEscherichia coliO157:H7, influences intestinal colonization of calves and adherence to bovine primary intestinal epithelial cells

Abstract: Enterohaemorrhagic Escherichia coli (EHEC) comprise a group of zoonotic diarrhoeal pathogens of worldwide importance. Cattle are a key reservoir; however the molecular mechanisms that promote persistent colonization of the bovine intestines by EHEC are ill-defined. The large plasmid of EHEC O157:H7 encodes several putative virulence factors. Here, it is reported that the pO157-encoded Type V-secreted serine protease EspP influences the intestinal colonization of calves. To dissect the basis of attenuation, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…In agreement with a previous report suggesting that EspP is required for intestinal colonization in calves (20), we found that EspP interacts with fibronectin, indicating that EspP possesses lectin properties (Fig. 5C) and may recognize host proteins.…”
Section: Biochemical and Physical Properties Of The E Coli Ropes-cd supporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with a previous report suggesting that EspP is required for intestinal colonization in calves (20), we found that EspP interacts with fibronectin, indicating that EspP possesses lectin properties (Fig. 5C) and may recognize host proteins.…”
Section: Biochemical and Physical Properties Of The E Coli Ropes-cd supporting
confidence: 81%
“…EspC and EspP display enzymatic activities, and although EspC cleaves spectrin (also called fodrin) and hemoglobin, EspP of EHEC cleaves pepsin A, and human coagulation factor V (2,11,14,(17)(18)(19). The EspP protein was also shown to influence gut colonization in calves and contributes to adherence of EHEC to bovine primary rectal cells (20). Recently, EspP was found to be directly involved in biofilm formation and adherence of EHEC to T84 intestinal epithelial cells (21).…”
mentioning
confidence: 99%
“…From the changes observed in the protein content of epithelium and mucus following larval challenge it is apparent that the in vitro model provided a technique which can be usefully deployed in investigations into recently established or immediate tissue responses to larval challenge. The use of the described enzymatic methodology for the isolation of epithelial cells from the gastric mucosa was based on the previously described method for the isolation of gastric crypts of bovine mucosa described by Dziva et al [4]. Cytospins confirmed that there was minimal contamination from non-epithelial lamina propria derived cells, compared to other methods used to isolate epithelial cells, such as mucosal scrapings and the use of EDTA (preliminary data, not included here), and only minimal contamination with albumin was observed in 2-D gels.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the enzymatic dispersion of the epithelial cells was two-fold: (i) to release the larvae that were closely associated to the gastric mucosa, and (ii) to achieve dispersion of epithelial cells for the proteomic analysis. The enzymatic dispersion was based on the method described by Dziva et al [4].…”
Section: In Vitro Model and Sample Preparationmentioning
confidence: 99%
“…What drives the selection of particular genes to create a STEC pathogen is unknown. However, because the existence of a primarily bovine animal reservoir of infection is a major difference between STEC and other pathotypes of E. coli, some genes, such as ehxA and espP, may be acquired by STEC to facilitate survival and persistence in the bovine gut (37,38). Therefore, although some determinants may not be considered essential virulence factors for human infection, they may confer an advantage to STEC survival and transmission in a different environment, such as an animal reservoir of infection.…”
Section: Discussionmentioning
confidence: 99%